A217 SIMETHICONE DECREASES BLOATING AND IMPROVES BOWEL PREPARATION EFFECTIVENESS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (15th March 2019) - Moolla, M; Dang, J; Shaw, A; Dang, T; Tian, C; Karmali, S; Sultanian, R
Abstract: Background: We performed a systematic review and meta-analysis to determine if the addition of simethicone to bowel preparations prior to colonoscopy had an impact on bowel cleanliness and patient tolerability. Simethicone is an adjunct frequently used but there is currently no consensus on whether it should be recommended for routine use in combination with standard bowel preparations. Furthermore, mounting evidence suggests that simethicone adheres to the lining of the working channel on some of the endoscopes despite reprocessing, leading to the formation of biofilms. Given conflicting evidence regarding the effectiveness of simethicone as an adjunct to bowel preparation combined with recent data suggesting simethicone may contribute to biofilm formation, it is important to reassess the potential benefits of simethicone when added to bowel preparation regimes prior to colonoscopy. Aims: 1. Determine the effectiveness of simethicone as an adjunct to bowel preparation on bowel cleanliness Methods: A comprehensive search was conducted for studies that compared colon cleansing of patients that received standard bowel preparation alone and in combination with simethicone prior to colonoscopy. Only randomized controlled trials were included. The primary outcomes were colon cleanliness and tolerability. Meta-analysis was performed to compare the number of successful bowel preparations amongst patients receiving polyethylene glycol (PEG) versus patients receiving PEG + simethicone. For tolerability, rates of nausea, vomiting, abdominal pain, and abdominal bloating were compared amongst patients receiving PEG versus patients receiving PEG + simethicone. Results: Sixteen randomized controlled trials with 5630 patients were included in meta-analysis. Overall, PEG with simethicone improved colon cleansing compared with PEG alone (OR 1.48, CI 1.11 to 1.97, P = 0.008). This improvement was seen in patients receiving single dosing (OR 1.83, CI 1.20 to 2.79, P = 0.005) but not in patients receiving split dosing (OR 1.32, CI 0.72 to 2.43, P = 0.38). The rates of nausea (OR 0.96, CI 0.75 to 1.24, P = 0.75), vomiting (OR 1.00, CI 0.69 to 1.44, P = 0.99), and abdominal pain (OR 0.69, CI 0.40 to 1.18, P = 0.17) were not significantly different between PEG and PEG + simethicone cohorts. For abdominal bloating, the PEG cohort had greater odds of experiencing bloating than the PEG + simethicone cohort (OR 2.33, CI 1.70 to 3.20, P < .00001). Conclusions: Simethicone, when combined with PEG, resulted in superior colon cleanliness compared to PEG alone. However, this improvement was not seen in patients receiving split-dose PEG, which is now the standard of care. Furthermore, simethicone decreased abdominal bloating but has no effect on nausea, vomiting, and abdominal pain. Funding Agencies: None